Genetic Silencing of Fatty Acid Desaturases Modulates α-Synuclein Toxicity and Neuronal Loss in Parkinson-Like Models of C. elegans - Maulik, Malabika; Mitra, Swarup; Basmayor, Ajiel Mae; Lu, Brianna; Taylor, Barbara E.; Bult-Ito, Abel (Frontiers in Aging Neuroscience, 2019)
The molecular basis of Parkinson’s (PD) disease is currently unknown. There is increasing evidence that fat metabolism is at the crossroad of key molecular pathways associated with the pathophysiology of PD. Fatty acid desaturases catalyze synthesis of saturated fatty acids from monounsaturated fatty acids thereby mediating several cellular mechanisms that are associated with diseases including cancer and metabolic disorders. The role of desaturases in modulating age related neurodegenerative manifestations such as PD is poorly understood. Here we investigated the effect of silencing Δ9 desaturase enzyme encoding fat-5 and fat-7 genes which are known to reduce fat content, on α-synuclein expression, neuronal morphology and dopamine related behaviors in transgenic PD-like models of C. elegans. The silencing of the fat-5 and fat-7 genes rescued both degeneration of dopamine neurons and deficits in dopamine-dependent behaviors, including basal slowing and ethanol avoidance in worm models of PD. Similarly, silencing of these genes also decreased the formation of protein aggregates in a nematode model of PD expressing α-synuclein in the body wall muscles and rescued deficits in resistance to heat and osmotic stress. On the contrary, silencing of nhr-49 and tub-1 genes that are known to increase total fat content did not alter behavioral and pathological endpoints in the PD worm strains. Interestingly, the genetic manipulation of all four selected genes resulted in differential fat levels in the PD models without having significant effect on the lifespan, further indicating a complex fat homeostasis unique to neurodegenerative pathophysiology. Overall, we provide a comprehensive understanding of how Δ9 desaturase can alter PD-like pathology due to environmental exposures and proteotoxic stress, suggesting new avenues in deciphering the disease etiology and possible therapeutic targets.